The strange case of eugenics: A subject's ontogeny in a long-lived classification scheme and the question of collocative integrity. - Tennis, Joseph T. (Journal of the American Society for Information Science & Technology, 2012)
This article introduces the problem of collocative integrity present in long-lived classification schemes that undergo several changes. A case study of the subject 'eugenics' in the Dewey Decimal Classification is presented to illustrate this phenomenon. Eugenics is strange because of the kinds of changes it undergoes. The article closes with a discussion of subject ontogeny as the name for this phenomenon and describes implications for information searching and browsing.